Celebrity Endorsement, Perceived Risk, and Purchase Intention: The Moderating Role of Brand Image - Kamelia Vanny Danaswari; Aprihatiningrum Hidayati (Jurnal Aplikasi Bisnis dan Manajemen, 2024)
Background: The rapid advancements in technology, information, and communication have significantly impacted the global economy, including the competitive landscape of businesses.Purpose: This study explores the influence of celebrity endorsement and perceived risk on consumer purchase intention towards local Indonesian skincare products, emphasizing the moderating role of brand image. Design/methodology/approach: The study used a quantitative survey targeting local skincare users in the Jabodetabek area, collected via Google Forms, and analyzed using SPSS 26 with multiple and moderated regression analysis. This research provides new insights into the Indonesian skincare market, highlighting the dual impact of celebrity endorsement and perceived risk on purchase intention, with a focus on brand image's moderating role.Findings/Result: The findings reveal that celebrity endorsement and perceived risk significantly, yet distinctly, influence purchase intention. Importantly, brand image was found to moderate the impact of celebrity endorsement on purchase intention, but did not significantly alter the effect of perceived risk on the same. These results have substantial implications for skincare marketers, suggesting that investments in celebrity endorsement, when combined with robust brand image strategies, and targeted marketing addressing perceived risks, can significantly influence consumer decision-making, thereby enhancing engagement and purchase intention in the competitive skincare market. Conclusion: Celebrity endorsement significantly increases purchase intention, and while brand image moderates this effect, it does not significantly change the impact of perceived risk.Originality/value (State of the art): This research provides new insights into the Indonesian skincare market, highlighting the dual impact of celebrity endorsement and perceived risk on purchase intention, with a focus on brand image's moderating role. Keywords: brand image, celebrity endorsement, perceived risk, purchase intention, local skincare market